Erratum: Nurturing families: A feasibility randomised controlled trial of a whole-family intervention with vulnerable families in Jordan - ERRATUM - Brown, Felicity L; Yousef, Hind; Bleile, Alexandra C E; Mansour, Hadeel; Barrett, Anna; Ghatasheh, Maha; Puffer, Eve S; Mansour, Zeinab; Hayef, Karam; Kurdi, Samer; Ali, Qaasim; Tol, Wietse A; et al. (Global mental health, 2024)
[This corrects the article DOI: 10.1017/gmh.2024.43.].